IL-2-induced proliferative response is controlled by loci Cinda1 and Cinda2 on mouse chromosomes 11 and 12: a distinct control of the response induced by different IL-2 concentrations - Krulová, M; Havelková, H; Kosarová, M; Holán, V; Hart, A A; Demant, P; Lipoldová, M (Genomics, 1997)
Lymphocytes of mouse strains BALB/cHeA (BALB/c) and STS/A (STS) differ in the IL-2-induced proliferative response, STS being a high and BALB/c a low responder in the range of concentrations 125-2000 IE/ml. We analyzed the genetic basis of this strain difference using the recombinant congenic (RC) strains of the BALB/c-c-STS/Dem (CcS/Dem) series. This series comprises 20 homozygous strains all derived from two parental inbred strains: the "background" strain BALB/c and the "donor" strain STS. Each CcS/Dem strain contains a different, random set of approximately 12.5% genes of the donor strain STS and approximately 87.5% genes of the background strain BALB/c. In this way, the STS genes controlling the IL-2-induced response became separated into individual CcS/Dem strains, as indicated by differences in the magnitude of the IL-2-induced response among CcS/Dem strains (M. Lipoldová et al., 1995, Immunogenetics 41: 301-311). To map some of these genes, we tested F2 hybrids between one of the high-responder RC strains, CcS-4, and the low-responder parental strain BALB/c. We found that the response to high IL-2 concentrations is controlled by a locus, Cinda1 (cytokine-induced activation 1), on chromosome 11 near the marker D11Mit4. The response to a lower dose of IL-2 tested on lymphocytes of the same mice was found to be controlled by another locus, Cinda2, in the centromeric part of chromosome 12, the higher response being linked to the STS allele of the marker D12Mit37. Understanding the action of genetic factors, such as Cinda1 and Cinda2, that control T cell function is expected to contribute to the efficient analysis of the genetic control of susceptibility to infections and autoimmune diseases.
Keywords: Recombinant Proteins; geny MHC třídy II; Chromosome Mapping; Interleukin-2; Lymphocyte Activation; myši inbrední BALB C; Genetic Linkage; aktivace lymfocytů; T-lymfocyty; Mice, Inbred BALB C; genetické markery; rekombinantní proteiny; imunologická odpověď na dávku; Animals; lidé; interleukin-2; genetická vazba; mapování chromozomů; Humans; zvířata; Hybridization, Genetic; myši; T-Lymphocytes; hybridizace genetická; Genes, MHC Class II; Alleles; Dose-Response Relationship, Immunologic; Mice; alely; Genetic Markers